ASUHAN KEPERAWATAN JIWA PADA PASIEN DENGAN CORE PROBLEM ISOLASI SOSIAL DI RS X - Kiranti, Anisa Sekar; Pasaribu, Jesika (Journal Healthcare Education, 2025)
Mental illness is a condition in which a person's mental functioning is altered, resulting in decreased mental performance and creating distress for the individual or hindering the performance of their social roles. Individuals suffering from mental illness generally experience difficulties in building relationships with those around them. Clients often tend to stay away from their social environment, making it difficult for them to interact with others. This condition is known as social isolation. Social isolation is a state where a person feels alone, which is perceived to be caused by others and seen as a negative and threatening situation. The consequences of social isolation can include social withdrawal, irritability, unpredictable behavior, hallucinations, as well as lack of attention to oneself. The purpose of this case study is to identify the success of providing social isolation implementation strategies. The method used was a case study involving the nursing process including assessment, data analysis, nursing diagnosis, intervention planning, implementation, evaluation, and observation. This case study was conducted for 10 days of monitoring. Interventions in this study were carried out through direct demonstration. The results of the intervention carried out on the patient showed a decrease in symptoms of social isolation in the individual.